2008
DOI: 10.1080/00330120701724087
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage Breast Cancer Diagnosis and Health Care Access in Illinois∗

Abstract: The variations of breast cancer mortality rates from place to place reflect both underlying differences in breast cancer prevalence and differences in diagnosis and treatment that affect the risk of death. This article examines the role of access to health care in explaining the variation of late-stage diagnosis of breast cancer. We use cancer registry data for the state of Illinois by zip code to investigate spatial variation in late diagnosis. Geographic information systems and spatial analysis methods are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(159 citation statements)
references
References 46 publications
7
147
0
5
Order By: Relevance
“…While our findings are consistent with a large body of literature documenting the association of poorer health outcomes with increasing percent of local residents who are Black, and with racial segregation, [47][48][49][50][51][52][53][54][55][56] they run counter to findings from the emerging literature that focuses exclusively on these exposures' relationship to breast cancer mortality. Haas et al 15 found no relationship between racial segregation (operationalized as isolation) and breast cancer mortality, and Warner and Gomez 16 found an inverse relationship between Black neighborhood racial composition and breast cancer mortality among Black women and a positive relationship for White women, controlling for metropolitan segregation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While our findings are consistent with a large body of literature documenting the association of poorer health outcomes with increasing percent of local residents who are Black, and with racial segregation, [47][48][49][50][51][52][53][54][55][56] they run counter to findings from the emerging literature that focuses exclusively on these exposures' relationship to breast cancer mortality. Haas et al 15 found no relationship between racial segregation (operationalized as isolation) and breast cancer mortality, and Warner and Gomez 16 found an inverse relationship between Black neighborhood racial composition and breast cancer mortality among Black women and a positive relationship for White women, controlling for metropolitan segregation.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have found that people who had a greater distance from their residence to mammography facility were diagnosed at a more advanced cancer stage. 49,50 Other possible mediators include (1) poorer quality of care at facilities that were located near predominately Black areas, 51 and (2) governmental and corporate disinvestment from predominately Black areas that produces increased exposure to hazards and stressors, and diminished access to treatment opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…11, Figure 1 shows the summary of criteria used for inclusion of eligible studies in this review. Of the eligible papers selected, 23 were from the United States, two each from Australia and New Zealand, and one each from Canada, Denmark, Egypt, Estonia, Italy, Poland, South Africa, Switzerland, and the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…6 Other studies on cancer survival from cancer in various countries have noted that geographical location is strongly associated with survival and that could also reflect stage at diagnosis and the kind of treatment patients are likely to receive. [7][8][9][10][11][12][13] In contrast, some studies have reported that no significant difference exists between breast cancer stage at diagnosis and place of residence or travel time/ distance travel to the nearest mammography facility. [14][15][16][17][18][19][20][21][22] The aim of this review was to examine systematically the literature on the effect of geographical location variation on breast cancer stage at diagnosis, race/ ethnicity, and socioeconomic status rather than rural-urban differences in mammography use or risk factors for breast cancer development.…”
mentioning
confidence: 94%
See 1 more Smart Citation